Effectiveness of diet therapy for patients with diabetes mellitus (Research, Society and Development, 2020)
Diabetes Mellitus (DM) can be defined as a disorder of multiple etiologies resulting from defects and ineffectiveness of insulin secreted by the pancreas causing insulin resistance. Non-drug treatment includes some strategies, such as: lifestyle change and eating habits. This study aimed to highlight through a literature review the benefits of diet therapy for patients with diabetes mellitus. This is an integrative literature review, for its construction we used the following databases: Scielo, VHL and Google academic. The study was able to show that the proper and balanced dietary treatment, with fiber-rich legume consumption, allows further improvements in glycemic control, insulin resistance, lipid profile, among others. It was also observed that individuals with healthy eating habits had a lower risk of diabetes mellitus-associated diseases when compared to patients with unhealthy eating practices.